Model-driven generation of artificial yeast promoters - Benjamin J. Kotopka (Nature Portfolio, 2020)
A small set of promoters is used for most genetic construct design in S. cerevisiae. Here, the authors develop a predictive model of promoter activity trained on a data set of over one million sequences and use it to design large sets of high-activity promoters.